Psychological factors influencing post-traumatic growth in caregivers of breast cancer patients - Mahbobeh Faramarzi; Mohammad Golparvar Azizi; Neda Ahangari; Daryush Moslemi; Ehsan Jalalian; Farzan Kheirkhah; Hemmat Gholinia; Seyed Mohsen Jafari (BMC Palliative Care)
Abstract Introduction Some family caregivers of breast cancer patients experience post-traumatic growth, which is influenced by various psychological factors. However, limited studies have explored these factors. This study aims to examine the psychological factors affecting post-traumatic growth in primary caregivers of breast cancer patients. Methods This cross-sectional study was conducted on 194 primary caregivers of breast cancer patients at a referral oncology hospital in Mazandaran Province (Babol, Iran). Participants completed questionnaires assessing post-traumatic growth, Hospital Anxiety and Depression Scale, the NEO Five-Factor Inventory, Perceived Social Support, Perceived Stress Scale, and Spiritual Well-Being. Correlation matrices were used to evaluate the relationships between psychological factors and post-traumatic growth, and stepwise regression analysis identified predictors of post-traumatic growth. Results The prevalence of post-traumatic growth (77.3%) among caregivers of breast cancer patients was higher than anxiety (47.9%) and depression (22.2%). post-traumatic growth was negatively associated with perceived stress, depression, anxiety, and neuroticism, while it was positively correlated with extraversion, agreeableness, conscientiousness, and spiritual well-being (p-value < 0.05). Stepwise regression analysis revealed that conscientiousness (β = 0.285, p-value < 0.001) and spiritual well-being (β = 0.209, p-value = 0.002) were positive predictors of post-traumatic growth, whereas perceived stress (β = -0.150, p-value = 0.025) was a negative predictor. Conclusion Spiritual health and high conscientiousness are facilitators, while stress is a barrier to post-traumatic growth (PTG) in caregivers of breast cancer patients. These findings emphasize the need to consider psychological factors in clinical interventions to support caregivers.